Growth and Nutrient Utilization of Clarias gariepinus Fed Dietary Levels of Jackbean (Canavalia ensiformis) Meal - Anyanwu, D.C.; Umeh, O.I.; Nnadozie, H.C.; Ogwo, V.O.; Okafor, E.O. (Pakistan Journal of Nutrition, 2012)
Clarias gariepinus fingerlings of average weight 0.71 g were sourced from ARAC, Port Harcourt and used to evaluate the effect of feeding dietary levels of Jackbean meal on growth and nutrient utilization of the fish. 35% isonitrogenous diets of 0%, 10%, 20% and 30% dietary levels of JBM were formulated. These were fed to the fingerlings randomly assigned to 4 treatments - TCN (Control), TJ1 (10% JBM), TJ2 (20% JBM) and TJ3 (30% JBM) respectively in 3 replicates of 13 fingerlings each, using 12 plastic aquaria of 250 × 150 cm dimension. The fish were fed at 5% body weight twice daily within the experimental period of 8 weeks. Mortality was highest in TJ3 and least in the control (TCN). Daily feed intake and protein intake were not significantly (p>0.05) different. The control (TCN) had the highest body weight gain, followed by TJ3, TJ1 and TJ2. Specific growth rate and feed conversion ratio of the treatments were not significantly (p>0.05) different. The protein efficiency ratio of treatment TJ3 was significantly (p<0.05) higher than the rest of the treatments. Dietary levels of JBM up to 30% inclusion level therefore had nutritional attributes as feedstuff in the diet of Clarias gariepinus fingerlings.